Adsorption/desorption process of formaldehyde onto iron doped graphene: a theoretical exploration from density functional theory calculations. Issue 6 (19th December 2016) - Cortés-Arriagada, Diego; Villegas-Escobar, Nery; Miranda-Rojas, Sebastián; Toro-Labbé, Alejandro
Abstract : A quantum chemical study was developed to show the adsorption and sensing ability of iron embedded graphene towards formaldehyde. Abstract : The interaction of formaldehyde (H2 CO) onto Fe-doped graphene (FeG) was studied in detail from density functional theory calculations and electronic structure analyses. Our aim was to obtain insights into the adsorption, desorption and sensing properties of FeG towards H2 CO, a hazardous organic compound. The adsorption of H2 CO was shown to be energetically stable onto FeG, with adsorption energies of up to 1.45 eV and favored in different conformations. This interaction was determined to be mostly electrostatic in nature, where the oxygen plays an important role in this contribution; besides, our quantum molecular dynamics results showed the high stability of the FeG–H2 CO interaction at ambient temperature (300 K). All the interactions were determined to be accompanied by an increase in the HOMO–LUMO energy gap with respect to the isolated adsorbent, indicating that FeG is highly sensitive to H2 CO with respect to pristine graphene. Finally, it was found that external electric fields of 0.04–0.05 a.u. were able to induce the pollutant desorption from the adsorbent, allowing the adsorbent reactivation for repetitive applications. These results indicate that FeG could be a promising candidate for adsorption/sensing platforms of H2 CO.